Exploring Best Practices in English Language Instruction for Primary Students - Yepi Sedya Purwananti (Universitas Nurul Jadid, 2026)
This study explores best practices in teaching English to young learners (TEYL) in Indonesian primary schools by examining teachers’ instructional approaches, classroom communication, management strategies, materials, assessment practices, and challenges. Employing a qualitative research design, data were collected through semi-structured interviews with experienced primary school English teachers. The data were analyzed using Braun and Clarke’s thematic analysis to identify recurring patterns and themes across participants’ perspectives. The findings reveal five major themes: the use of diverse and creative teaching methods, functional bilingual classroom communication, engagement-based classroom management, flexible use of teaching materials and assessment practices, and challenges accompanied by adaptive coping strategies. Teachers emphasized play-based and multi-sensory activities, such as songs, games, and storytelling, to enhance learners’ motivation and vocabulary development. The strategic use of the first language was found to support comprehension and reduce anxiety, while engagement-centered management fostered positive learning environments. Despite challenges including mixed-ability classrooms and limited parental involvement, teachers demonstrated pedagogical flexibility in adapting instruction to contextual constraints. These findings underscore the importance of child-centered, context-sensitive, and supportive approaches in TEYL and offer practical implications for teachers, schools, and teacher education programs